The interaction of regional legislative assembly and municipal representative authorities (on the materials of the Kaluga region) - M V Kostina (RUDN Journal of Public Administration, 2017)
The article is dedicated to the analysis of legal and organizational mechanisms of the interaction of the legislative assembly and municipal representative bodies. The accent is done on the connection between the mechanisms of the interaction of the regional and municipal representative bodies with the development of the federal legal base of functioning of municipalities and with the whole logic of the municipal reform. The difficulties of such interaction caused by the common problems of functioning of the municipalities are also mentioned. The article analyses the process of the development of the legal base of the municipalities of the Kaluga region and the practice of the interaction of regional legislative assembly and municipal regional representative bodies. The practice of the interaction is in the functioning of coordinating and advisory bodies (Advisory Council, Council of Young Deputies, Council of Non-Parliamentary Parties, Congress of Deputies of Representative Bodies of Municipal Entities) and also making seminars and meetings.